Down and Out in Eighteenth-Century London. - Hitchcock, Tim (Bloomsbury Publishing PLC, 2004)
London in the 18th century was the greatest city in the world. It was a magnet that drew men and women from the rest of England in huge numbers. For a few the streets were paved with gold, but for the majority it was a harsh world with little guarantee of money or food. For the poor and destitute, London's streets offered little more than the barest living. Yet men, women and children found a great variety of ways to eke out their existence, sweeping roads, selling matches, singing ballads and performing all sorts of menial labor. Many of these activities, apart from the direct begging.